Kepastian Hukum dan Implementasi Program Kemitraan Oleh Perusahaan Perkebunan Kelapa Sawit Berdasarkan Undang-Undang Nomor 20 Tahun 2008 Tentang Usaha Mikro Kecil Dan Menengah: (Studi Kasus: Keputusan Kppu Nomor: 03/Kppu-K/2021) - Aswan, Riel; Nachrawi, Gunawan (FOCUS, 2025)
The implementation of Law No. 20 of 2008 on Micro, Small, and Medium Enterprises (MSMEs) is essential for supporting sustainable partnerships between large companies and plasma cooperatives in the palm oil sector. This law aims to establish a core-plasma relationship model that is transparent, equitable, and focused on empowering MSMEs. However, challenges such as the dominance of large companies in decision-making, lack of financial transparency, and unmet plasma land obligations continue to hinder the law’s objectives. Supervision by the Business Competition Supervisory Commission (KPPU) and government support are expected to facilitate a more equitable partnership. This research employs a qualitative analysis method based on case studies, referencing KPPU Decision No. 03/KPPU-K/2021 and interview data regarding partnership practices. Additionally, literature review from journals and scientific sources was used to deepen the analysis. The findings show that KPPU's supervisory role is crucial in ensuring large companies' compliance with Law No. 20 of 2008. Government support through training and capacity-building is also needed to empower MSMEs. These findings demonstrate that consistent enforcement of the law can improve plasma cooperative welfare, support sustainable environmental practices, and enhance the international image of Indonesia’s palm oil industry. Therefore, improvements in the implementation of Law No. 20 of 2008 are necessary to achieve truly mutual benefits in partnerships.